1998
DOI: 10.5511/plantbiotechnology.15.217
|View full text |Cite
|
Sign up to set email alerts
|

A New Vector Set for GAL4-Dependent Transactivation Assay in Plants.

Abstract: To study transcriptional regulators, an in vivo functional assay is indispensable. Here we report a new convenient vector set for a transactivation assay in plants. The system consists of a luciferase reporter controlled by a synthetic promoter with GAL4-binding sites and an effector to express any fusion protein with the GAL4 DNA binding domain. Co-transfection of the two plasmids causes transactivation of the reporter by the expressed GAL4-effector fusion if the effector exhibits transcriptional activation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
42
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 11 publications
(17 reference statements)
1
42
0
Order By: Relevance
“…For transactivation assay, plasmids yy64 and yy96 were used as effector and reporter, respectively. 24) Each cDNA fragment of AtbZIP60 was amplified by PCR using following primers:…”
Section: Methodsmentioning
confidence: 99%
“…For transactivation assay, plasmids yy64 and yy96 were used as effector and reporter, respectively. 24) Each cDNA fragment of AtbZIP60 was amplified by PCR using following primers:…”
Section: Methodsmentioning
confidence: 99%
“…The fact that antisense CIP4 only partially suppressed the cop1 mutations (Table 1) suggests the presence of a downstream pathway that bypasses CIP4. Among the identified downstream targets of COP1 (HY5 and CIP7), only HY5 is known to be involved in the regulation of hypocotyl elongation (Koornneef et al, 1980;Yamamoto et al, 1998). Therefore, HY5 might be involved in the predicted bypass pathway that acts in conjunction with CIP4.…”
mentioning
confidence: 99%
“…Therefore, CIP4 could be a transcriptional coactivator that does not recognize DNA directly but rather works together with another specific DNA binding factor. This would put CIP4 and CIP7 in the same class (Yamamoto et al, 1998), whereas HY5 would represent another group of transcription factors that bind promoter elements directly (Ang et al, 1998). Puente et al (1996) reported that combinatorial interactions of two distinct light-responsive promoter elements constitute an autonomous light-responsive determinant in CIP4: A Regulator of Photomorphogenesis 407 the promoter.…”
mentioning
confidence: 99%
“…For DNA staining, samples were incubated with 1 mg/ml 4Ј,6-diamino-2-phenylindole (DAPI) solution before observation. The GAL4BD-PTF1 effector plasmid was constructed by fusing a cDNA encoding AtPTF1 with the GAL4 DNA binding domain in a yy64 vector, a derivative of pMA560 (Yamamoto and Deng 1998). AtPTF1 was subcloned into the BglII/SalI sites and yy64 vector alone was used as a control.…”
mentioning
confidence: 99%
“…AtPTF1 was subcloned into the BglII/SalI sites and yy64 vector alone was used as a control. The reporter plasmid, yy96, contained a luciferase gene placed under control of the GAL4 binding site (Yamamoto and Deng 1998). An internal control plasmid, containing a Renilla luciferase (R-Luciferase) gene placed under control of the 35S-CaMV promoter was used to normalize for differences in bombardment efficiency.…”
mentioning
confidence: 99%